Detection of T91 Steel Corrosion with a Fe3+-Enhanced Fluorescence Probe - Tie Feng Xia; Li Zhang; Da Quan Zhang; Li Xin Gao (Journal of Chemistry)
We study a rhodamine-based fluorescent compound (FD2) as corrosion indicator for T91 steel in 3% NaCl solution. FD2 has a desirable property of “turn-on” fluorescence emission via forming a complex with Fe3+ ions. The varying of fluorescence intensity is linked to that of weight-loss of T91 steel. Early attack on T91 steel was detected using fluorescence microscopy. This nondestructive method of initial corrosion detection can be used during maintenance before serious damage happens.